2020
DOI: 10.3390/plants9020173
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Botanical Insecticide and Entomopathogenic Fungi on Pest Mortality and the Behavioral Response of Its Natural Enemy

Abstract: Sustainable agricultural intensification employs alternatives to synthetic insecticides for pest management, but these are not always a direct replacement. Botanical insecticides, for example, have rapid knockdown but are highly labile and while biological pesticides are more persistent, they are slow acting. To mitigate these shortcomings, we combined the entomopathogenic fungus (EPF) Metarhizium anisopliae with pyrethrum and evaluated their efficacy against the bean aphid, Aphis fabae. To ascertain higher tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Several studies have reported that neem products also have an inhibitory effect on these EPF (Rogerio et al 2005) by suppressing the fungal growth and spore germination (Castiglioni et al 2003). The surprising effect of fungi M. anisopliae when used alone repelled the parasitoid, Aphidius colemani of Aphis fabae, but by combining with pyrethrum, it had no negative effect on the parasitoid (Fernández-Grandon et al 2020).…”
Section: Synergism Between Botanicals and Entomopathogenic Fungimentioning
confidence: 95%
See 3 more Smart Citations
“…Several studies have reported that neem products also have an inhibitory effect on these EPF (Rogerio et al 2005) by suppressing the fungal growth and spore germination (Castiglioni et al 2003). The surprising effect of fungi M. anisopliae when used alone repelled the parasitoid, Aphidius colemani of Aphis fabae, but by combining with pyrethrum, it had no negative effect on the parasitoid (Fernández-Grandon et al 2020).…”
Section: Synergism Between Botanicals and Entomopathogenic Fungimentioning
confidence: 95%
“…Metarhizium anisopliae was also considered to be synergistic when used in combination with botanicals viz. neem (Shoukat et al 2016), pyrethrum (Fernández-Grandon et al 2020), and 1-chlorooctadecane (Hussain and AlJabr 2020). The combination of pyrethrum and M. anisopliae (1 × 10 8 CFU/mL) reduced the Aphis fabae survival by 29.2 h, representing their synergistic activity (Fernández-Grandon et al 2020).…”
Section: Synergism Between Botanicals and Entomopathogenic Fungimentioning
confidence: 98%
See 2 more Smart Citations
“…It is of global importance to survey and describe insect pathogens ( Hyde et al, 2019 ). Entomopathogenic fungi can act as natural enemies of agricultural pests and play an important role in maintaining ecological balance ( Fernández-Grandon et al, 2020 ; Sobczak et al, 2020 ). For example, fungal pathogens such as, Coelomomyces, Culicinomyces , and Lagenidium have the capacity to kill larva and adult mosquitoes, reducing their host population ( Scholte et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%